The purpose-driven university : transforming lives and creating impact through academic social responsibility - Haski-Leventhal, Debbie (Bingley, U.K. : Emerald Publishing Limited, 2020)
What is the purpose of universities, and what is their role in our world? Many would say that it is to educate students and conduct research. This is true, but somehow, the narrow focus on these two goals led universities to be perceived as ivory towers and detached elitist institutions. In an era when many organisations shift towards purpose, responsibility, and sustainability, universities have a role to play in becoming a force for good. While many higher education institutions are focused on being the best for the world, some are changing to become the best for the world. A movement has begun. A purpose-driven university utilises its resources, knowledge, talent and people to continuously and intentionally contribute to the communities and the environment in which it operates: through research, education, programmes and service. This timely book offers the why, how and what of a purpose-driven university, utilising cases, research, concepts and a framework which can be implemented in any university interested in making a difference. This book tells the stories of purpose-driven universities and other organisations, and serves as a call for action by academic leadership to change higher education for good.
Includes index.
Print version record.
Keywords: Universities and colleges; Social responsibility of business; Educational leadership; Education -- Higher; Universities